Foreign experiences of effective measures for modernization of the tax system - Nomazov Bakhrom Bobomuradovich (THE INNOVATION ECONOMY, 2026)
The article examines the need to improve our national tax practice by effectively adopting effective measures for tax system modernization in the tax practice of foreign countries. Also, as a result of studying foreign experiences regarding effective measures for tax system modernization, conclusions and proposals for tax system modernization were developed.